The AIR Learning Model (Auditory, Intellectual, Repetition): Its Effectiveness in Enhancing Student Learning Engagement - Sholehah, Tika Fahmiyati; Asiah, Nur; Yusnita, Erni (Papanda Publisher, 2025)
Student engagement in learning represents a critical indicator of educational quality, yet many Islamic Religious Education programs continue to struggle with low participation rates and passive learning environments. This study investigated the effectiveness of the AIR (Auditory, Intellectual, and Repetition) learning model in enhancing student learning engagement, specifically focusing on students' ability to express ideas during classroom activities. A quasi-experimental design with posttest-only control group was employed involving 62 Grade XI students at SMK Nurul Falah Pugung, Indonesia. Participants were randomly assigned to experimental (n=31) and control (n=31) groups, receiving AIR model instruction and conventional direct instruction respectively. Learning engagement was measured using a validated questionnaire focusing on the